2013
DOI: 10.17795/compreped-4528
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Oral and IM Dexamethasone Efficacy in Croup Treatment

Abstract: Background: Croup, or acute laryngotracheobronchitis, is the most common cause of upper airway obstruction in children. Objectives: In this study, the efficacies of intramuscular and oral dexamethasone administration are compared for treatment of croup. Patients and Methods: This is a single-blind randomized trial involving 68 children divided into two groups, the first group received 0.6 mg/kg intramuscular dexamethasone and the second group received 0.6 mg/kg oral dexamethasone. The clinical score, respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Soleimani et al, in a study to compare the effect of DM treatment of muscle by snapping on 68 children with croup, who were randomly divided into 2 groups, clinical symptoms, respiratory rate, heart rate, saturation of oxygen and response to treatment was measured. It was concluded that intramuscular and oral dexamethasone had same effect, but because of the non-invasiveness, oral route was used [12]. Most studies show the effectiveness of intramuscular dexamethasone in croup, but recent studies have shown that inhaled corticosteroids are also effective in the treatment for croup.…”
Section: Discussionmentioning
confidence: 99%
“…Soleimani et al, in a study to compare the effect of DM treatment of muscle by snapping on 68 children with croup, who were randomly divided into 2 groups, clinical symptoms, respiratory rate, heart rate, saturation of oxygen and response to treatment was measured. It was concluded that intramuscular and oral dexamethasone had same effect, but because of the non-invasiveness, oral route was used [12]. Most studies show the effectiveness of intramuscular dexamethasone in croup, but recent studies have shown that inhaled corticosteroids are also effective in the treatment for croup.…”
Section: Discussionmentioning
confidence: 99%
“…Across various levels of croup severity, all these methods, whether it was intramuscular, intravenous, oral, or inhaled, proved to be effective. Support for these findings also comes from a randomized controlled trial (RCT) performed in Iran [4,5]. In another study focusing on outpatient care, oral dexamethasone was compared with oral prednisolone in the treatment of 87 children with mild to moderate croup symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…The optimal type of corticosteroid, route of administration, and dose have remained unclear. Trials comparing parenteral, oral, and nebulized routes of steroid delivery in croup have demonstrated that intramuscular, intravenous, oral, and inhaled routes of administration of glucocorticoids are effective in croup of all levels of severity, including one randomized-controlled trial carried out in Iran 4 , 5 . For this reason, oral corticosteroids are the preferred route unless oral intake is not possible.…”
Section: Introductionmentioning
confidence: 99%